# Prove Wilson's theorem by Lagrange's theorem

• Apr 9th 2010, 05:27 PM
kingwinner
Prove Wilson's theorem by Lagrange's theorem
Lagrange's Theorem: let p be any prime and $f(x) = a_nx^n +a_{n-1}x^{n-1} + ... + a_1x + a_0$ with $a_n$ ≡/≡ 0 (mod p). Then f(x) 0 (mod p) has at most n solutions.

Use the above theorem to prove Wilson's theorem.
Hint: Let $f(x) = (x-1)(x-2)...(x-(p-1)) - (x^{p-1} - 1)$ for an odd prime p.

Proof:
Expanding,
$f(x) = (x-1)(x-2)...(x-(p-1)) - (x^{p-1} - 1)$
= $a_{p-2}x^{p-2} +...+ a_1x + a_0$ where the $a_i$ are some coefficients
By the above theorem, f has at most p-2 roots mod p IF $a_{p-2}$ ≡/≡ 0 (mod p). (*)
But by Fermat's theorem, for a=1,2,...,p-1, $a^{p-1} -1$ ≡ 0 (mod p).
So for a=1,2,...,p-1, f(a) ≡ 0 (mod p).
So f has at least p-1 roots mod p. (**)
(*) and (**) contradict unless f(x) ≡ 0 (mod p). Therefore, we must have f(x) ≡ 0 (mod p).
=> f(0)=(-1)(-2)...(-(p-1)) - (-1) ≡ 0 (mod p)
=> $(-1)^{p-1} (p-1)! + 1$ ≡ 0 (mod p)
For odd primes p, p-1 is even, so (p-1)! ≡ -1 (mod p)
(For p=2, check directly.)
=========================================

I don't understand the two lines in red.
I understand that there is a contradiction, but why does this imply that f(x) ≡ 0 (mod p)? Why in this case, there will be no contradiction? I'm totally lost here...

Also, f(x) ≡ 0 (mod p) doesn't necessarily mean it holds for EVERY integer x, so why can we substitute x=0 and say that f(0) ≡ 0 (mod p)? What is the justification for this step?

I hope someone can explain this proof.
Thank you very much!

[also under discussion in math link forum]
• Apr 9th 2010, 09:41 PM
chiph588@
Look at Lagrange's Theorem here. It's a tiny bit different than what you said. Hopefully that clears things up for you.
• Apr 10th 2010, 01:07 PM
FancyMouse
A typical proof is that, use the same polynomial f(x), argue that it has degree at most p-2, so if f(x) is not the zero polynomial, then it must have at most p-2 roots. But then argue that 1~p-1 are all roots, so f(x)=0 (mod p) (here the equality means f(x) equals the zero polynomial, not LHS=RHS when you plug in every number mod p). Then compute the constant term of f(x) and you'll get Wilson.

The proof that OP presents involves $a_{p-2}$, which is definitely confusing since it is always 0 mod p if p is odd prime, and it does nothing to prove the theorem.